THE IMPORTANCE AND ROLE OF THE PRODUCTION AND SOCIO-ECONOMIC POTENTIAL OF AN ECONOMIC ENTITY IN THE CURRENT BUSINESS ENVIRONMENT - Schneider, V.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
At present, a lot of attention is paid to issues of economic importance, since economic, social, and environmental situations require continuous clarification. In turn, adjustments are made by external and internal business conditions that require updating of conceptual and methodological tools for assessing the level of aggregate potential, both for an individual economic entity and for the country as a whole. In this regard, it is necessary to pay more attention to production, socio-economic, resource, and intellectual potential. On the basis of analytical studies, a method of reliable assessment of the effective use of all types of potential should be built. Without begging for the dignity of each of the above types of potential, let us pay attention to the production and socio-economic potential of economic entities involved in increasing the sustainable development of economic entities. Currently, there are several methodological approaches to determining the level of the total potential of an economic entity. The most important ones include: integrated assessment of indicators; comprehensive analysis of the effectiveness of potential use through additive and multiplicative criteria. In addition, it is advisable to base production potential on maximizing potential opportunities for product quality, cost, and delivery, which is provided by indicators of production flexibility, innovation (especially in the context of bringing new products to market), and reproducibility. An important problem is the problem of determining the internal reserves of socio-economic development, which is becoming increasingly relevant in modern conditions and requires improving the methodology for analyzing the socio-economic potential. Therefore, the development of theoretical and practical approaches and methodological principles for a comprehensive assessment of all types of potential causes some discussion and requires new developments that take into account changes in the external and internal conditions for the functioning of economic entities.